Analisis Framing Aktor Politik Di Media Sosial Tiktok: Studi Pada Akun Tiktok Helmi Hasan Channel - Rocki Pratama, Rocki Pratama; Novliza Eka Patrisia (STAI Bumi Silampari, 2025)
This research aims to analyze how political messages are constructed, disseminated, and responded to by audiences on the dynamic TikTok platform. Using a qualitative approach and an in-depth single-case study design, this research focuses on a comprehensive analysis of video content and public interactions occurring on the @helmihasanchannel account. Primary data was collected through participant observation and online document studies, including video transcriptions and screen recordings of user comments. The research, using Todd Gitlin's Framing theory, shows that @helmihasanchannel successfully leveraged TikTok's unique characteristics to create an emotional connection with the public. This is evident in its use of a relaxed communication style and everyday narratives. The uploaded content covers issues of infrastructure development and social assistance, which significantly stimulated public responses in the form of comments and likes. The use of TikTok features such as background music, filters, effects, duets, and stitching also increased the content's appeal. Content framing strategies were used to build positive perceptions, such as showcasing road construction as evidence of tangible performance.